EXPERIENTIAL MARKETING AND BUSINESS INNOVATION AFFECTING CUSTOMER LOYALTY IN CAFE BUSINESS - CHAWKRADIAN, Suntaraporn; LALAENG, Chanyaphak (Asian Administration and Management Review, 2023)
The objective of this research was to investigate the causal variables of experiential marketing and business innovation affecting the customer loyalty in cafe business. The study was conducted with population living in Chumphon, Thailand who used to use the cafe business services. The results of multiple regression analysis revealed that experiential marketing, which includes Sense, Feel, Think, Act, and Relate, and the loyalty towards café business services, aimed to test hypotheses H1a-H1e found that all five aspects of experiential marketing significantly influenced customer loyalty to café business services at the 0.05 level. Hence, the hypotheses H1a-H1e were accepted. However, the independent variables of experiential marketing in all five aspects collectively predict and explain the dependent variable, which is customer loyalty to coffee shop businesses, with an efficiency of 57.9%. Business innovation, which includes product innovation, process innovation, service innovation, and marketing innovation, and the loyalty towards café business services, aimed to test hypotheses H2a-H2d found that all four aspects of business innovation significantly influenced customer loyalty to café business services at the 0.05 level. Hence, the hypotheses H2a-H2c were accepted. In this case, the independent variables from all four business innovation aspects jointly predict and explain the dependent variable, which is customer loyalty to coffee shop businesses, with an efficiency of 62.11%.